Phylogenetic characterization and in situ localization of the bacterial symbiont of shipworms (Teredinidae: Bivalvia) by using 16S rRNA sequence analysis and oligodeoxynucleotide probe hybridization. - Distel, D L (1991)
It has been proposed that a bacterium isolated from the gills of shipworms (teredinid mollusks) is, by virtue of its ability both to degrade cellulose and to fix dinitrogen, the symbiont that enables these mollusks to utilize wood as their principal food source. The phylogenetic affiliation of four of these bacteria isolated from wood-boring bivalve mollusks was determined by 16S rRNA sequence analysis by using the reverse transcriptase method with six oligodeoxynucleotide primers. The four bacterial strains tested had indistinguishable 16S rRNA sequences, supporting the previous conclusion, based on phenotypic characterization, that these isolates represent a single species. Evolutionary distance matrix analysis of the RNA sequence indicated that the bacterial symbiont falls within the gamma-3 subdivision of the Proteobacteria and is distinct from other known bacterial genera. In situ localization of the bacterial symbiont in tissue sections of the shipworm Lyrodus pedicellatus was determined by using a 16S rRNA-directed oligodeoxynucleotide hybridization probe specific for the bacterium isolated from shipworm gill tissue. Fluorescence microscopy showed that the specific probe bound to L. pedicellatus tissue at sites coincident with the location of symbiont cells and that it did not bind to other host tissues. This technique provided direct visual evidence that the cellulolytic, nitrogen-fixing bacterial isolates were the symbionts observed within the gill of L. pedicellatus.